Reactive strength endurance: Part 2 Is maximal reactive strength associated with reactive strength endurance? - Browne, D.; Flanagan, E. (Sport Performance & Science Reports, 2018)
The results of this study provide some weight that plyometric training aimed at increasing reactive strength may have positive e ects on performance under fatigue. - Higher levels of reactive strength is associated with greater absolute expression of RSI during a fatigue protocol. Essentially RSIMAX o ers a protective e ect on performance. - Practitioners can apply Relative RSE60 and/or Absolute RSE60 to describe the reactive endurance capabilities of their athletes/sports. - A note of cation should be applied, as intensive stretch shortening exercise often results in reversible muscle damage (12). However, a shortened assessment could be used such as a 0 { 20 second protocol where a moderate decrease in reactive strength was observed in part 1 (1). - In the present study, over 80% of the variance in absolute RSE60 was explained by RSIMAX. Considering this, one may deem that solely assessing RSIMAX in the 10-to-5 repeated jump test may o er enough insight into absolute RSE abilities. Only assessing RSIMAX however, will not o er any insight into relative reactive strength endurance qualities.